Stock Status Estimating of 5 Shark Species in the Waters Around Taiwan Using a Length-Based Bayesian Biomass Estimation (LBB) Method - Ju, Peilong; Chen, Mingru; Tian, Yongjun; Zhao, Yu; Yang, Shengyun; Xiao, Jiamei (Frontiers in Marine Science, 2020)
Five shark stocks in the waters around Taiwan were assessed using the LBB method, addressing the present gap. Among them, only one filter-feeding shark, megamouth shark Megachasma pelagios, qualified as having a healthy status. Of the remaining filter-feeding shark, whale shark Rhincodon typus, was seriously overexploited, possibly even collapsed, spadenose shark Scoliodon macrorhynchos, and other two large sharks (dusky shark Carcharhinus obscurus and silky shark Carcharhinus falciformis) were also overexploited. These stock status estimates for the five shark species using the LBB method were consistent with international agreements such as IUCN, CITES and CMS.